Revisiting Tamban Beach: Exploring Gender's Influence on Place Attachment and Subsequent Intentions - Purwitasari, Hanifah Wahyu; Dinanti, Dian; Hidayat, Ar Rohman Taufiq (Journal of Regional and Rural Studies, 2025)
This study examines the influence of gender on how tourists' emotional ties to a destination, often referred to as "place attachment," shape their likelihood of returning. Focusing on Tamban Beach, a coastal destination in Malang, East Java, Indonesia, currently experiencing a significant decline in visitor numbers, the research highlights the crucial importance of understanding the motives for repeat visits to boost tourism development. Methodologically, a quantitative study was conducted, collecting data from 120 tourists on-site. Participants completed self-administered questionnaires during their weekend visits throughout February 2025. The central analysis involved applying Spearman's rank correlation to discern the overall relationship between place attachment and revisit intentions and, critically, to compare the strength of this association specifically within male and female tourist cohorts. The results highlight a strong and statistically significant positive correlation between place attachment and revisit intentions across the entire sample of respondents. However, a significant divergence emerged when considering gender: male tourists showed a much stronger positive correlation (approximately 76%) between their preference for Tamban Beach and their propensity to return, in contrast to female tourists (approximately 51%). This outcome suggests that, for men, a deep emotional connection with the destination acts as a remarkably direct and powerful catalyst for future visits. On the other hand, while women also establish undeniable positive connections, their revisit decision-making process appears to be determined by a broader and more complex context of influencing factors. This research critically illustrates the need to consider gender in the field of tourist behavior studies. Finally, the information gathered provides practical and actionable advice to destination managers, allowing them to design more targeted and effective strategies to increase visitor loyalty and encourage repeat visits.